Impact of Grape Temperature at Pressing on Organic Acids and Oenological Characteristics of Méthode Cap Classique Wines - Chidi, B.S.; Mafata, M.; Notshokovu, N.Z.; van Jaarsveld, F. (South African Journal of Enology and Viticulture, 2018)
Maintaining the chemical composition of a wine is essential for the wine industry. Although the sugar-acid balance of a wine is of primary sensory importance, individual acids and oenological parameters are equally important. The main focus of this study was to investigate the impact of grape temperature at harvest, on the oenological volatile acidity (VA), titratable acidity (TA), pH and alcohol levels and organic acid (citric, malic, pyruvic and succinic) characteristics of Méthode Cap Classique (MCC) wines during winemaking, produced from grape cultivars obtained from two regions. Chardonnay and Pinot noir grapes were obtained from Robertson (warmer) and Elgin (cooler) regions and were subjected to different temperature treatments, i.e. 0, 10, 25 and 30oC before further processing, including pressing, primary fermentation, blending, tirage, secondary fermentation, riddling and disgorging. Grape temperature was mostly responsible for a significantly higher pH of Robertson (0 and 10ºC) and lower pH (0ºC) of Elgin post-tirage wines. Chardonnay base wines from both regions that were vinified from grapes at lower temperatures (0 and 10oC) were richer in malic- and succinic acid, while Pinot noir wines from both regions were characterised by higher malic-, citric- and pyruvic acid. Pyruvic acid was only detected after the secondary fermentations in wines from both regions. To our knowledge, this study is the first to investigate the influence of grape temperature on the oenological and organic acid characteristics of MCC wines in different regions, and throughout different production stages.